'Apparently the chap is a bit of a rogue': Upgrading risk in non-emergency telephone calls to the police. Issue 1 (5th March 2018) - Rock, Frances
Abstract : This paper examines how risk communication features in telephone calls to one British non-emergency police number. Using a collection of naturally occurring telephone calls to a police non-emergency line the paper takes an approach grounded in qualitative discourse analysis. The work illustrates that callers discursively construct risk through categories which enable them to make sense of, and meaning around, dangers they perceive. Through this discursively constructed risk, callers warrant their calls. In doing so, they draw on categorisations of crime types and then upgrade their categorical alignments, which serves to connect the incidents they are reporting to increasingly serious crime type categories. The paper shows how this process of construction and categorisation of risk is bound into wider discursive strategies. The work has applications in call handling contexts where an understanding of ways that risk can be appropriated has diagnostic potential.